Performance of Charcoal Coconut Shell Ash in the Asphalt Mixture under Long Term Aging - Putra Jaya, Ramadhansyah; Mohd Rosli, Hainin; Khairil Azman, Masri; Youventharan, Duraisamy; Ekarizan, Shaffie (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Improvement in transportation system is never been as easy as just providing links for better connection and network but more to do with the pavement quality of the road itself. Modification with agriculture waste is just another approach to enhance the performance of asphaltic concrete. In this study, a non-traditional bitumen modifier from a coconut shell which is the charcoal coconut shell ash (CCSA) was used. Addition of CCSA in bitumen with 0%, 2%, 4%, 6%, and 8% by weight of bitumen were investigated along with the laboratory stimulation of aging was applied in this study. Properties of modified asphalt mixture were determined using resilient modulus, dynamic creep and Marshall Stability test. Results of samples with CCSA which underwent aging show some improvement in terms of the stability and permanent deformation characteristics. Resilient modulus, dynamic creep and Marshall Stability tests recorded the highest rates when compared to controlled sample. Hence, for more durable asphalt concrete and high serviceability it is recommended to use 2% to 4% of CCSA.